Does the 'Economic Explanation' Work? Settlement, Agriculture and Erosion in the Territory of Halieis in the Late Classical-Early Hellenistic Period - Acheson, Phoebe E. (Journal of Mediterranean Archaeology, 1998)
This paper examines the landscape and archaeological sites around fourth- and third-century BC Halieis, in the Southern Argolid, Greece, exploring the ancient agricultural economy in all its socio-economic variety and micro-environmental variability. It is a re-study of the Late Classical Early Hellenistic period as described in the publications of the Southern Argolid Survey, and challenges conclusions drawn there about the economic focus of this region, its predominant agricultural practices, and the relationship between settlement expansion and soil erosion. It is suggested that previous publications have emphasized the construction of general models to the neglect of analysis of specific historical situations. In-depth analysis of data from a regional study project of the sort undertaken here, concentrating on the historical and economic situation of one specific period, can allow a nuanced and detailed understanding of human-land interactions, especially if archaeological and environmental information is synthesized.